Managing Contextual Complexity in an Experiential Learning Course: A Dynamic Systems Approach through the Identification of Turning Points in Students' Emotional Trajectories - Nogueiras, Gloria; Kunnen, E. Saskia; Iborra, Alejandro (Frontiers in Psychology, 2017)
This study adopts a dynamic systems approach to investigate how individuals successfully manage contextual complexity. To that end, we tracked individuals’ emotional trajectories during a challenging training course, seeking qualitative changes – turning points - and we tested their relationship with the perceived complexity of the training. The research context was a five-day higher education course based on process-oriented experiential learning, and the sample consisted of 17 students. The students used a five-point Likert scale to rate the intensity of 16 emotions and the complexity of the training on 8 measurement points. Monte Carlo permutation tests identified 30 turning points in the 272 emotional trajectories analyzed (17 students * 16 emotions each). 83% of the turning points indicated a change of pattern in the emotional trajectories that consisted of: a) increasingly intense positive emotions or b) decreasingly intense negative emotions. These turning points also coincided with particularly complex periods in the training as perceived by the participants (p = 0.003, and p = 0.001 respectively). The relationship between positively-trended turning points in the students’ emotional trajectories and the complexity of the training may be interpreted as evidence of a successful management of the cognitive conflict arising from the clash between the students’ prior ways of meaning-making and the challenging demands of the training. One of the strengths of this study is that it provides a relatively simple procedure for identifying turning points in developmental trajectories, which can be applied to various longitudinal experiences that are very common in educational and developmental contexts. Additionally, the findings contribute to sustaining the assumption that complex contextual demands lead unfailingly to incomplete learning by individuals’ learning is incomplete. Instead, it is how individuals manage complexity which may or may not lead to learning. Finally, this study can also be considered a first step in research on the developmental potential of process-oriented experiential learning training.